Dermatofibrosarcome de Darier Ferrand sous orbitaire: Une localisation rare [Dermatofibrosarcoma Darier Ferrand under orbital: A rare location] - Aboubacar H. Bambara; Amina N Ouedraogo; Nina A Ouedraogo Nde; Vincent B Ili; Jérôme Sanou; Achach Thouraya Chtioui; Tarticus Konsem (Our Dermatology Online, 2016)
Dermatofibrosarcoma protuberans (DFS) is a rare malignant skin tumor, characterized by local aggressiveness, significant potential for recurrence and a low risk of distant metastasis. The location under the eyes, not yet reported in the literature may involve the functional and aesthetic prognosis. We report a case.